2022
DOI: 10.54530/jcmc.543
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge on Drug Abuse Among MBBS First Year Students of Chitwan Medical College

Abstract: Background: Currently, drug abuse is booming in developing countries including Nepal, which may directly affect personal as well as socioeconomic condition of individual and community. Teenage, being the most crucial stage of life, is the age when teenagers want to explore a lot of things and is curious about new experiments. So, they think that, drugs assist them to overcome all the problems they face in day to day life. Therefore, the aim of this study was to assess the knowledge regarding drug abuse among M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…8,11 Our study revealed that bad relationship between parents and children (60%) followed by friends pressure (40.2%) as a reason to start drugs, another study explored in Chitwan, Nepal the consistent findings which depicts that Majority of the participants were familiar about the main cause as teenage curiosity/peer pressure, relationship between parents and child (96.9%). 12 The consistent findings was found in which majority of respondent responded causes of drug abuse is bad relationship with family, to feel relax, failed in exam and film stars and idols which are shown on television. 13,11 This parallel findings could be because of familiarly with in our socio cultural context.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…8,11 Our study revealed that bad relationship between parents and children (60%) followed by friends pressure (40.2%) as a reason to start drugs, another study explored in Chitwan, Nepal the consistent findings which depicts that Majority of the participants were familiar about the main cause as teenage curiosity/peer pressure, relationship between parents and child (96.9%). 12 The consistent findings was found in which majority of respondent responded causes of drug abuse is bad relationship with family, to feel relax, failed in exam and film stars and idols which are shown on television. 13,11 This parallel findings could be because of familiarly with in our socio cultural context.…”
Section: Discussionsupporting
confidence: 59%
“…8 On the contrary, study conducted by Paudel, Chaurasia, Bhurtyal & Karki, Begum & Devi has shown no any significant association between these variables. 9,10 On the contrary, other study conducted by Bhattarai & Chudal has shown a significant association between these variables. This inconsistent findings may be due to different study population and setting.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations